Reducing Missed Opportunities: Pairing Sexually Transmitted Infection Screening With Syringe Exchange Services. Issue 11 (November 2016) - Roth, Alexis M.; Goldshear, Jesse L.; Martinez-Donate, Ana P.; Welles, Seth; Chavis, Martha; Van Der Pol, Barbara
Abstract : Abstract: About 17.5% of sexually active injection drug users recruited from a syringe exchange in Camden, NJ (n = 120) screened positive for chlamydia/gonorrhea. Among these cases, 40% were detected via extragenital screening. This pilot demonstrates that colocating sexually transmitted infection control with syringe exchange leads to sexually transmitted infection case finding. Abstract : We piloted a sexually transmitted infection screening program at a syringe exchange. Prevalence of chlamydia/gonorrhea among 120 injection drug users was 17.5%. Results indicate sexually transmitted infection and syringe exchange services can be effectively.